Information Flow Between Heart Rhythm, Repolarization, and the Diastolic Interval Series for Healthy Individuals and LQTS1 Patients - Ozimek, Mateusz; Żebrowski, Jan J.; Baranowski, Rafał (Frontiers in Physiology, 2021)
Using information theoretic measures, relations between heart rhythm, repolarization in the tissue of the heart and the diastolic interval time series is analyzed. These processes are a fragment of the cardiovascular physiological network. A comparison is made between the results for 84 (42 women) healthy persons and 65 (45 women) LQTS1 patients. Self-entropy, transfer entropy and joint transfer entropy are calculated for the three time series and their combinations. The results for self-entropy indicate the well-known result that variability of heart rhythm for the healthy is larger than that of QT interval series. The flow of information depends on the direction with the flow from the heart rhythm to QT dominating. In LQTS1 patients, However, our results indicate that information flow in the opposite direction may occur – a new result. The information flow from the heart rhythm to QT dominates which verifies the asymmetry seen by Porta et al. (Porta et al., 2017) in the variable tilt angle experiment. The amount of new information and self entropy for the LQTS1 patients are smaller than for the healthy. However, information transfers from RR to QT and from DI to QT are larger in case of LQTS 1 patients.